2012
DOI: 10.1111/j.1423-0410.2012.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis E virus infection in Ghanaian blood donors – the importance of immunoassay selection and confirmation

Abstract: Background and Objectives  Hepatitis E virus (HEV) infection is emerging as a potential new threat to blood safety after several cases of transfusion–transmission were reported from non‐epidemic countries. On the basis of seroprevalence data, HEV is endemic in Ghana where poor sanitary conditions and regular flooding are prevalent. However, no data are available for HEV prevalence in blood donors. Materials and Methods  Plasma samples from 239 Ghanaian blood donors were tested for anti‐HEV IgG and IgM by ELISA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 46 publications
5
18
4
Order By: Relevance
“…HEV serological assays have allowed seroprevalence studies, which provide useful surveillance data on the distribution of this virus, and have also assisted with identifying risk factors for exposure to HEV. However, studies have shown variability in estimates with different commercial assays [21, 28], and the results presented herein are consistent with such findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…HEV serological assays have allowed seroprevalence studies, which provide useful surveillance data on the distribution of this virus, and have also assisted with identifying risk factors for exposure to HEV. However, studies have shown variability in estimates with different commercial assays [21, 28], and the results presented herein are consistent with such findings.…”
Section: Discussionsupporting
confidence: 90%
“…Studies with different commercial HEV IgG enzyme immunoassays have shown variability in sensitivity [2628]. A study using anti-HEV reference serum (from the World Health Organisation) and including known HEV cases has shown 98% seropositivity with the Wantai IgG assay compared to 56% with the Genelabs IgG assay [27].…”
Section: Introductionmentioning
confidence: 99%
“…Seroprevalence varies by country from 84.3% [55] among pregnant Egyptian women aged 24 years on average to 0% among village residents aged 24 years on average in Gabon [72]. The seroprevalence seems to be higher in pregnant women than in the general population in Ghana (28.7% [78] vs. 4.6% [76]) and also in Gabon (14.2% [73] vs. 0% [72]). Two studies of Ghanaians suggest that predominant HEV genotypes in that country may be of zoonotic origin: seroprevalence among pig handlers is over 34% [75,77] whereas that among general population is about 4% [76].…”
Section: Resultsmentioning
confidence: 99%
“…However, all PCR assays were negative, HEV immunoassays are prone to false reactivity [61], [62], and none of the patients showed both IgM and IgG. Usually, both serological markers and HEV RNA are present during acute infection ([62], [63] and validation data for the test used in this study [64]).…”
Section: Discussionmentioning
confidence: 99%